2013
DOI: 10.1016/j.semcdb.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The genomically mosaic brain: Aneuploidy and more in neural diversity and disease

Abstract: Genomically identical cells have long been assumed to comprise the human brain, with post-genomic mechanisms giving rise to its enormous diversity, complexity, and disease susceptibility. However, the identification of neural cells containing somatically generated mosaic aneuploidy – loss and/or gain of chromosomes from a euploid complement – and other genomic variations including LINE1 retrotransposons and regional patterns of DNA content variation (DCV), demonstrate that the brain is genomically heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 226 publications
(272 reference statements)
1
85
0
Order By: Relevance
“…This could in turn be related to the genomic heterogeneity of the mature brain, thought to be a source of neural diversity (Bushman and Chun, 2013). In the ferret, the extent of S‐phase shortening is greater than in the mouse (Arai et al, 2011); this could be a consequence of the greater progenitor number and neuron output of a gyrencephalic brain, especially during the generation of supragranular layers, compared with a lissencephalic one.…”
Section: Discussionmentioning
confidence: 99%
“…This could in turn be related to the genomic heterogeneity of the mature brain, thought to be a source of neural diversity (Bushman and Chun, 2013). In the ferret, the extent of S‐phase shortening is greater than in the mouse (Arai et al, 2011); this could be a consequence of the greater progenitor number and neuron output of a gyrencephalic brain, especially during the generation of supragranular layers, compared with a lissencephalic one.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that PCD plays an important role in buffering error or noise in several aspects of neural development. Indeed, it has been reported that many aneuploid cells are generated in mouse embryonic cerebral cortex development and that this phenomenon is greatly increased by inhibition of apoptosis during development (Bushman and Chun, 2013;Peterson et al, 2012;Rehen et al, 2001). Although how and why neural aneuploidy originates spontaneously in mammalian brain development remains unclear, these results suggest that endogenous PCD in the cerebral cortex, if not all of the nervous system, may arise from somatic genomic alterations.…”
Section: Pcd: a Reflection Of Inevitable Developmental Error And Noise?mentioning
confidence: 99%
“…Although how and why neural aneuploidy originates spontaneously in mammalian brain development remains unclear, these results suggest that endogenous PCD in the cerebral cortex, if not all of the nervous system, may arise from somatic genomic alterations. PCD may thus serve as a quality control mechanism to eliminate cells that have undesirable genomic alterations ( Figure 4D) (Bushman and Chun, 2013;Peterson et al, 2012). Hereafter, we will further discuss the quality control function, in other words, buffering action, of PCD by considering the potential triggers of PCD, namely developmental error, noise, or intrinsic developmental programs.…”
Section: Pcd: a Reflection Of Inevitable Developmental Error And Noise?mentioning
confidence: 99%
“…Aneuploidy is an abnormal number of copies of a genomic region, which is often observed not only in tumor cells but also in human brain, particularly during development (Bushman and Chun, 2013;Iourov et al, 2012). However, hyperploid neurons are not only just a feature of the developing brain but also exist in the healthy adult at an estimated frequency of about 10% (Bushman and Chun, 2013;Iourov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%